Early Acute Liver Failure In Severe Acute Hepatitis B - Gontar Alamsyah Siregar (The Indonesian Society for Digestive Endoscopy, 2002)
Early acute liver failure is defined by the presence of a drop below 50% of the normal prothrombine ratio, jaundice, and clotting factors of less than 50% in any patient with acute liver disease. Clinical features and laboratory manifestations of viral hepatitis range from unapparent disease, asymptomatic infection, to culminant disease, which has the highest mortality rate of up to over 80 %. We report a case of a 22-year old man who was treated in a private hospital with early acute liver failure caused by hepatitis B infection. The diagnosis was based on clinical symptoms and laboratory test Results such as jaundice, hepatomegaly, ascites, 34% prothrombine ratio, elongated prothrombine time (37,1 seconds), hypoalbuminemia (1,9 g/dL), hyperbillirubinemia (total billirubin 26,35 mg/dL, direct billirubin 16,66 mg/dL, HbsAg (+), IgM anti- HBc (+), IgM anti HAV (-), and anti HCV (-). The patient suffered from jaundice for 6 weeks and on the third week, he suffered from ascites. He had improved clinical condition and laboratory test results with conservative therapy after the seventh week. At the end of the tenth week, the patient’s clinical condition and laboratory test results had reached normal, with HBsAg (-) and HBsAb (+). Whether or not interferon should have been given to this patient is still arguable. Key words: Early acute liver failure, Severe acute hepatitis B